Vietnam National and Provincial Primary Health Care Scorecards - World Bank (World Bank, Washington, DC, 2020)
This report aims to provide insights into how health services are delivered at the grassroots level to support the expansion of access to quality health services in Vietnam with a focus on primary health care (PHC). It intends to identify any challenges in this area and emphasize the importance of tracking performance and accountability for the resources spent. The focus of this report is aligned with the efforts of the ministry of health (MOH) to strengthen the grassroots health system and, hence, with the World Bank’s larger engagement in Vietnam on primary care strengthening. This study used the framework developed by the PHC performance initiative (PHCPI) to organize the scorecard based on specific performance domains and pre-identified core indicators, complemented or adjusted to the Vietnamese context. The indicators were grouped into a national scorecard and a provincial scorecard, which was piloted in two provinces, Bac Giang and Yen Bai. Vietnam has achieved impressive health gains with the reduction of under-five mortality (U5M) rate and maternal mortality ratio (MMR) and an increase in life expectancy; however, it needs to accelerate progress if it is to meet the health-related sustainable development goals (SDGs). Vietnam has made significant achievements in increasing the coverage of many maternal and child health (MCH) services; however, nutrition indicators are lagging behind and data are scarce on coverage of noncommunicable disease (NCD) services.